Development of Mathematics Teaching Modules Based on Differentiated Instruction to Stimulate Student Engagement - Sadrack Luden Pagiling; Anis Munfarikhatin; Irmawaty Natsir; Ayulia Rombe Ma'dika (Didaktik Matematika, 2024)
Student engagement is one of the students predictors for achieving more robust performance in mathematics, and it can be promoted by differentiated instruction. Therefore,this research aimed to develop a valid, practical, and effective mathematics module based on differentiated instruction to stimulate student engagement. Employing the ADDIE model, the research was conducted at one lower secondary school involving 22 eighth-grade students. We collected data through validity assessment sheets to test validity, teacher and student response questionnaires to test practicality, and student engagement observation sheets to test the practicality of teaching modules. The validity of the module was confirmed through V-Aikens method, proving that the module satisfied the valid category. Findings demonstrate that modules are in the valid category and are very practical categories in the teacher response and the student response questionnaire. In addition, this module effectively stimulates student engagement in cognitive, behavioral, and emotional engagement logically, with the results of the observation sheet of student engagement in the engaged and very engaged categories. Thus, the mathematics teaching module based on differentiated instruction is declared valid, practical, and effective in stimulating student engagement.